Water Encyclopedia 2004
DOI: 10.1002/047147844x.ww317
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment and Recycling Technologies

Abstract: Due to the continuous population growth, uneven distribution of water resources, periodic droughts, and water pollution, it is very important to develop water treatment and recycling technologies for economic, effective, and fast water treatment and reclamation. Different types of water treatment and recycling techniques and their basic principles, applications, costs, maintenance, and suitability are discussed. In addition, a systematic approach to water treatment and recycling, involving understanding, evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…17,18 Initially, activated carbon was used for the removal of pollutants from water, which has been replaced by some cost-effective adsorbents. 55,56 In the last two decades, nanotechnology has developed with its applications in almost all branches of science and technology. In this series, water treatment is not deprived of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Initially, activated carbon was used for the removal of pollutants from water, which has been replaced by some cost-effective adsorbents. 55,56 In the last two decades, nanotechnology has developed with its applications in almost all branches of science and technology. In this series, water treatment is not deprived of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, in spite of some limitations, it will be a good water treatment technology in the near future. Much work has been carried on the removal of different pollutants from water by using adsorption batch modes. , Initially, activated carbon was used for the removal of pollutants from water, which has been replaced by some cost-effective adsorbents. , In the last two decades, nanotechnology has developed with its applications in almost all branches of science and technology. In this series, water treatment is not deprived of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%